Analyzing sexual violence in Photocopier films: A multimodal discourse approach - Fiardi, Rahma Khairunnisa; Agung, Lingga; Putra, Wibisono Tegar Guna (Universitas Padjadjaran, 2024)
Background: The increase in sexual violence cases in Indonesia has prompted filmmakers to explore similar themes in their works. Unlike conventional films that explicitly depict rape as a manifestation of sexual violence, “Photocopier” (2021) takes a unique approach by portraying it through symbolic and metaphorical means, making it more challenging for audiences to comprehend. Purpose: This study aims to examine how “Photocopier” (2021) visualizes various forms of sexual violence in selected scenes. Methods: A qualitative approach was employed for this research. The analysis focused on acts of sexual violence depicted in several scenes of the film “Photocopier,” utilizing Andrew Burn’s theory of multimodal discourse analysis, specifically the kineikonic mode. This mode classifies the sign systems within motion media or film into three categories: embodied mode, visual mode, and auditory mode. Results: “Photocopier” (2021) illustrates sexual violence through a variety of forms, including sexual harassment, sexual exploitation, sexual intimidation, and sexual control. Implicit depictions of sexual harassment are seen, for instance, through the victim’s clothing being worn inside out. Sexual exploitation is portrayed through the sale of personal data and photographs of victims for financial gain, driven by the perpetrator’s sexual desires. Additionally, forms of intimidation and sexual control are demonstrated through the judgment imposed on victims of sexual violence who are unaware of their situation and the forcible collection of evidence with sexual undertones. Implications: This study underscores the importance of raising public awareness about the diverse manifestations of sexual violence, particularly those depicted in films, thus enhancing understanding and vigilance towards such issues.